Binary liquid film condensation from water-ammonia vapors mixture flowing downward along a parallel plate condenser - Nasr, Abdelaziz; Nassif, Ahmed; Al-Ghamdi, Abdulmajeed S. (Frontiers in Mechanical Engineering, 2023)
The water-ammonia mixtures is used as an efficient working fluid in industrial applications such as plate condenser, air-conditioning, heat pumps, separation processes, refrigeration and absorber/generator heat exchange. The present work focuses on a numerical investigation of water-ammonia condensation on a falling binary liquid film inside a parallel plate condenser by mixed convection. The parallel plate condenser is composed by two parallel vertical plates. One of the plates is wetted by nanofilm and cooled by the thermal flux cooling while the other plate is isothermal and dry. Parametric computations were performed to investigate the effects of the inlet parameters of gas, the properties of the binary liquid film as well as the thermal flux cooling on the combined mass and heat transfer and on the efficiency of the parallel plate condenser. The results show that an increase in the inlet vapor of ammonia as well as of vapor water enhances the efficiency of the parallel plate condenser. It is shown also that an enhancement of efficiency of the parallel plate condenser has been recorded when the thermal flux cooling and inlet liquid flow rate is elevated. Whereas the increase of the inlet liquid concentration of ammonia inhibits the efficiency of the parallel plate condenser.